2010 23rd IEEE Computer Security Foundations Symposium 2010
DOI: 10.1109/csf.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Strong Invariants for the Efficient Construction of Machine-Checked Protocol Security Proofs

Abstract: Abstract-We embed an operational semantics for security protocols in the interactive theorem prover Isabelle/HOL and derive two strong protocol-independent invariants. These invariants allow us to reason about the possible origin of messages and justify a local typing assumption for the otherwise untyped protocol variables. The two rules form the core of a theory that is well-suited for interactively constructing natural, human-readable, correctness proofs. Moreover, we develop an algorithm that automatically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…We found that proof generation times are similar, but our proof checking times are orders of magnitude faster, ranging from a factor 10 to a factor 1700. These results also apply here, as our new implementation is as fast as the one used in [32].…”
Section: Related Worksupporting
confidence: 52%
See 1 more Smart Citation
“…We found that proof generation times are similar, but our proof checking times are orders of magnitude faster, ranging from a factor 10 to a factor 1700. These results also apply here, as our new implementation is as fast as the one used in [32].…”
Section: Related Worksupporting
confidence: 52%
“…In our previous work on decryption-chain reasoning [32], we provided a detailed timing comparison to their approach. We found that proof generation times are similar, but our proof checking times are orders of magnitude faster, ranging from a factor 10 to a factor 1700.…”
Section: Related Workmentioning
confidence: 98%
“…The interpretation mapping a message pattern to its corresponding message in the context of a thread i and the variable store σ is modeled by the family of partial functions inst σ,i : Pat Msg. In the semantics presented in [30,31], these functions were total. However, we now use partial functions because the lookup of a shared symmetric long-term key always fails if one of the variables is not instantiated to an agent name.…”
Section: A1 Bidirectional Keysmentioning
confidence: 99%
“…The Scyther-proof tool [113] uses a variant of the algorithm presented in this book. The main additional feature is that it generates proof scripts for use with the Isabelle-HOL theorem prover [129].…”
Section: Scyther-proofmentioning
confidence: 99%